THE INFLUENCE OF THE PANDEMIC ON THE YASINAN TRADITION OF THE INDONESIAN SOCIETY - Muhamad Restu Andhika Esa Putra; Ahmad Ruslan (IAIN Batusangkar, 2021)
The Coronavirus pandemic has been running for over 1 year, subsequently, numerous customs and ropensities for the Indonesian public have changed. One of the changing local area customs is the yasinan custom, this practice is regularly held by Indonesian individuals one time each week. In this custom where individuals assemble and read Surah Yasin together, however this get-together practice is exceptionally opposing to be done as of now during the pandemic and when the PSBB was carried out. Along these lines, the creator is keen on directing this examination, determined to perceive how much impact the pandemic has on the yasinan custom and how individuals manage it and keep up with the practice